College Students' Beliefs About Myths in Psychology - Axelrod, Michael I.; Helwig, Emily; Fruit, Nick; Jorgensen, Keith; Leichtnam, Brooklyn; Valima, Koren (My University, 2018)
The purpose of this study was to investigate undergraduate students’ beliefs about myths in psychology. We hypothesized that most college students would be able to discern myths from research-supported statements. However, we did believe students would endorse some myths as true, especially those that had long histories of exposure via the mass media, parents, and peers (e.g., school homicides are on the rise, low self-esteem is a major source of psychological problems; Furnham & Hughes, 2014).
Color poster with text and table.
Keywords: Posters; Psychology; College students--Wisconsin--Eau Claire--Attitudes--Surveys; College students--Wisconsin--Eau Claire--Attitudes